The effect of alkali treatment on the mechanical properties of short pineapple leaf fibre (PALF) reinforced high impact polystyrene (HIPS) composites. - Siregar, Januar Parlaungan; Salit, Mohd Sapuan; Ab. Rahman, Mohamad Zaki; Mohd Dahlan, Khairul Zaman (WFL publisher, 2010)
This paper reported the study of the effect of the alkali (NaOH) treatment on the mechanical properties of pineapple leaf fibre (PALF) reinforced high impact polystyrene (HIPS) composites. The objective of this study was to investigate the effect of alkali (NaOH) treatment with different concentration of NaOH (0%, 2% and 4%) solution. The mechanical properties such as tensile strength, tensile modulus, flexural strength, flexural modulus, notched and unnotched impact and hardness of short pineapple leaf fibre (PALF) reinforced high impact polystyrene (HIPS) composites were studied and compared. NaOH concentration of 4% that was used for the short PALF treatment showed the highest mechanical properties value compared to the other concentration.